CLINICAL AND PARACLINICAL CHARACTERISTICS OF LACRIMAL GLAND LYMPHOPROLIFERATIVE DISORDERS AT THE VIETNAM NATIONAL EYE HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics of lacrimal gland lymphoproliferative disorders at the Vietnam National Eye Hospital.Subjects and methods: A cross-sectional descriptive study was conducted on 36 patients (50 eyes) diagnosed with lacrimal gland lymphoproliferative disease based on histopathological findings. All patients were examined and treated at the Oculoplastic Department, Vietnam National Eye Hospital, from May 2025 to November 2025.Results: The mean age was 58.8 ± 18 years, with the majority in the 61-80-year-old group; males accounted for 55.6%. The most common presenting symptom was a palpable mass (80.6%), followed by eyelid swelling (44.4%) and proptosis (22.2%). The most frequent clinical sign was a well-defined mass in the superotemporal orbit (88.9%), sometimes accompanied by eyelid edema (52.8%) and limitation of ocular motility (16.7%). On CT imaging, most lesions measured 2-4 cm (70%), were located in the superotemporal region (98-100%), showed homogeneous soft-tissue density with smooth margins (76%), well-defined borders (72%), mild globe indentation (84%), and no bone destruction (100%). Histopathologically, lymphomas accounted for 69.4% and lymphoid hyperplasia for 30.6%.Conclusion: Lacrimal gland lymphoproliferative disorders predominantly affect older adults and typically present as a superotemporal orbital mass. CT imaging features-homogeneous density, smooth margins, and absence of bone erosion-are suggestive, but histopathology remains the gold standard for diagnosis. The predominance of lymphomas highlights the importance of early detection and comprehensive evaluation to guide management.
Keywords: Lacrimal gland lymphoproliferative disorder, lymphoid hyperplasia, lacrimal gland lymphoma.